THE IMPACT DIMENSIONAL OF DELIMITERS ON TESTING AND TRAINING DUELS DRIBBLING IN YOUNG SOCCER (UNDER 15 YEAR) - Zerf, Mohammed; Bengoua, Ali (https://www.researchgate.net/publication/286454286_, 2015)
The delimiters are the most important tools, widely used in training and tests soccer, because they embodies the dimensions of the surface and the role of defender in major of the exercises for Soccer. That literature review 90% of soccer books use the smallest delimiters (plate) and 100% of our young soccer Algerians coaches (under 15 year) composed their sessions. from that the objective of our study focuses on the different forms and volumes of these last lend, based on these differences our hypothesis confirms that they affected the information (indicators from the external environment) and qualities coordinators during the change of direction(obstruction of the upper body player). Our experience is based on a practicalprotocol of Vankersschaver Jacques1982 from his study entitled "Role of Visual Index and Cognitive Process in the Acquisition of a Gesture Football Technique”. Were we have introducing the different kinds of delimiters (fig1) and the inactive player to determine the most type of delimiter appropriate to evaluate and train duels with ball in young soccer. Were our finding confirmed: (1) The mannequin is the most delimiter appropriate for testing and progress in duels soccer. (2) The progress in training duels requires the smallest (familiar with the gest) arrive at the mannequin toperform with the gest (1vs1). (3) The objective of duels requires the involvement of the commitment of peripheral vision for information and central vision to master the ball. From that, the best dribbler is the player who lifts his head when he moves with the ball.
Keywords: Dimensions of delimiters, Duels, dribbling, young soccer under 15 year